2017
DOI: 10.1073/pnas.1615837114
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of Li 2 S on the surface of metal sulfides for Li−S batteries

Abstract: Polysulfide binding and trapping to prevent dissolution into the electrolyte by a variety of materials has been well studied in Li−S batteries. Here we discover that some of those materials can play an important role as an activation catalyst to facilitate oxidation of the discharge product, Li 2 S, back to the charge product, sulfur. Combining theoretical calculations and experimental design, we select a series of metal sulfides as a model system to identify the key parameters in determining the energy barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
916
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,088 publications
(988 citation statements)
references
References 42 publications
(43 reference statements)
36
916
0
2
Order By: Relevance
“…Cui and co‐workers found that metal sulfides accelerate the oxidation of Li 2 S to sulfur ( Figure 6 ). 12 Electrochemical measurements and XPS studies show that VS 2 , CoS 2 , and TiS 2 have higher binding energies toward Li 2 S 6 . First‐principles calculations show that the strong interaction between LiPSs and metal sulfides lowers the overpotential for the Li 2 S decomposition.…”
Section: Catalytic Metal‐based Hosts For Li–s Batteriesmentioning
confidence: 95%
“…Cui and co‐workers found that metal sulfides accelerate the oxidation of Li 2 S to sulfur ( Figure 6 ). 12 Electrochemical measurements and XPS studies show that VS 2 , CoS 2 , and TiS 2 have higher binding energies toward Li 2 S 6 . First‐principles calculations show that the strong interaction between LiPSs and metal sulfides lowers the overpotential for the Li 2 S decomposition.…”
Section: Catalytic Metal‐based Hosts For Li–s Batteriesmentioning
confidence: 95%
“…In particular, a sudden capacity drop was observed after the 50 th cycle, which was mainly attributed to the low utilization of sulfur and subsequent continuous formation of a large amount of insulating S/Li 2 S products during prolonged cycling. 46,47 A comparison of the different rate capabilities arising from the use of different electrolyte is given in Figure 7d. For all current densities, the cell using the 0.5 M LiTFSI electrolyte delivered a higher discharge capacity than the cell using the 1 M LiTFSI electrolyte.…”
Section: 45mentioning
confidence: 99%
“…The contents of Cu and S obtained from XPS results are much lower than added. [27,[34][35][36] A high ratio of pyridinic-N (41.3 % at. The XPS characterization technology only reflects the surface element information within the depth of 3 nm.…”
Section: Structural and Morphological Featuresmentioning
confidence: 99%